Mechanical properties of polysaccharide-based films for food packaging: a review - Bacca González, César Augusto; Molina Soler, Diana Edith; Guevara Guerrero, Beatriz (Revista Colombiana de Investigaciones Agroindustriales, 2023)
Seeking to find alternatives to reduce the misuse of polymers derived from hydrocarbons and their side effects on the environment. The aim of the following systematic literature review was to compare the tensile mechanical behavior of films made with chitosan, potato starch and hydroxypropylmethylcellulose (HPMC), used for packaging food products, comparing their average values of tensile stress, modulus of elasticity and deformation in breaking. The search was carried out in SCOPUS, Science Direct, Scielo, during 2013 - 2022, implementing different search equations. From the bibliographical study, it was analyzed that HPMC presents the best tensile mechanical properties (tensile strength: 32,44 MPa; strain at break: 17,37 %; modulus of elasticity: 305 MPa), closely followed by chitosan (tensile strength: 32,01 MPa; strain at break: 15,5 %; modulus of elasticity: 303,5 MPa) and, finally, potato starch (tensile strength: 10,56 MPa; strain at break: 11,89 %; modulus of elasticity: 395 MPa). It is hoped that this literature review will promote the development and application of polysaccharide-based films for food packaging by the industry as a strategy to solve environmental problems and for their optimal mechanical properties.